2006
DOI: 10.1245/s10434-006-9288-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Mutations and Imatinib Mesylate Response for 64 Taiwanese with Advanced GIST: Preliminary Experience from Chang Gung Memorial Hospital

Abstract: Activated mutation of kit constituted 90.7% genetic alteration of Taiwanese with advanced GIST and no PDGFRA mutation was detected. Imatinib induced a sustained objective response in more than half of Taiwan advanced GIST patients. ORR did not differ between patients whose GISTs had no mutation, kit exon 9, and 11 mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
6
18
1
Order By: Relevance
“…However, we did not find any differences in clinical outcome according to which codon of KIT exon 11 had undergone mutation. Consistent with our findings, a small study in Taiwanese patients found that clinical outcome to imatinib did not differ according to kinase mutational status [20]. The mutation rate for KIT in 54 Taiwanese GIST patients was 90.7%, and included 40 patients with KIT exon 11 mutations and nine patients with KIT exon 9 mutations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, we did not find any differences in clinical outcome according to which codon of KIT exon 11 had undergone mutation. Consistent with our findings, a small study in Taiwanese patients found that clinical outcome to imatinib did not differ according to kinase mutational status [20]. The mutation rate for KIT in 54 Taiwanese GIST patients was 90.7%, and included 40 patients with KIT exon 11 mutations and nine patients with KIT exon 9 mutations.…”
Section: Discussionsupporting
confidence: 89%
“…The higher relative dose of imatinib given to the Korean patients (using a fixed-dose strategy) could in part explain responses in these mutation-negative patients. The responses seen in Taiwanese patients are more similar to the results of the present study than to those of prior studies in western populations [13,14,20]. To confirm this hypothesis, a comparison of pharmacokinetic parameters between Asian and western GIST patients is needed.…”
Section: Discussionsupporting
confidence: 85%
“…VEGF expression has been shown previously to be related to aggressive tumor behavior in these tumors (19,20); however, it was not related to necrosis following imatinib treatment in our study. Although we showed a phenotypic correlation between CD34 and cystic change of GISTs following imatinib treatment, the precise roles of CD34 and VEGF in GISTs are not yet well understood and further studies will be required to elucidate functions of these molecules.…”
contrasting
confidence: 75%
“…Only 1/134 patients revealed a PDGFRα mutation in exon 12 and no mutations in the more prevalent exon 18 were identified (20,28). By contrast, a Chinese study was consistent with western trends described above (29).…”
Section: Kit Pdgfrα Number Of Studies/ ------------------------------supporting
confidence: 78%